Acute kidney injury impact on inpatient mortality in Clostridium difficile infection: A national propensity‐matched study. Issue 6 (26th February 2018) - Charilaou, Paris; Devani, Kalpit; John, Febin; Kanna, Sowjanya; Ahlawat, Sushil; Young, Mark; Khanna, Sahil; Reddy, Chakradhar
Abstract: Background and Aim: Acute kidney injury (AKI) is used as a marker of severity in Clostridium difficile infection (CDI) patients. We estimated the true effect of AKI in inpatient mortality of CDI patients, as there are no large‐scale, population‐based, propensity‐matched studies evaluating AKI's effect in this patient cohort. Methods: A retrospective observational study utilizing the National Inpatient Sample from years 2003 to 2012, including all adults with CDI, excluding cases missing data on age, inpatient mortality or gender. Trends and CDI‐related complications as mortality predictors were assessed using survey‐weighted multivariable regression. We estimated AKI's independent effect by propensity‐matching, post‐stratifying by chronic kidney disease status, allowing for multiple comorbidity adjustment. Results: A total of 2 859 599 patients with CDI were included, of which 896 122 (31.3%) had principal diagnosis of CDI. AKI prevalence was 22%. Mortality rate was 8.4%, while among AKI patients was higher (18.2%). In multivariable regression, AKI was associated with higher mortality (odds ratio [OR] = 3.16, 95% confidence interval [CI]: 3.02–3.30; P  < 0.001), while after propensity matching, AKI increased mortality by 86% (OR = 1.86, 95% CI: 1.79–1.94; P  < 0.001). CDI incidence increased by 1.8, together with the rate of AKI (12.6% in 2003 to 28.8% in 2012, P ‐trend < 0.001). Despite increasing hospitalizations, mortality over the study period decreased to 7.2% (2012) from 9.0% (2003); P ‐trend < 0.001. Conclusion: Hospital admissions of patients with CDI and concomitant AKI are increasing, but their inpatient mortality has improved over the study period. AKI is a significant contributor to mortality, independently of other comorbidities, complications, and hospital characteristics, emphasizing the need for early diagnosis and aggressive management in such patients.